2011
DOI: 10.1185/03007995.2011.582484
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability and efficacy of memantine add-on therapy to rivastigmine transdermal patches in mild to moderate Alzheimer's disease: a multicenter, randomized, open-label, parallel-group study

Abstract: There were no significant differences in tolerability and safety between the treatment groups. The combination therapy of memantine plus rivastigmine patch did not show an advantage over rivastigmine patch monotherapy on efficacy analyses. The sample size for comparing tolerability may have been too small to detect a difference of efficacy between the two groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 28 publications
(30 reference statements)
1
51
1
Order By: Relevance
“…The effect of concomitant memantine use on the efficacy, safety and tolerability of 9.5 mg/24 h rivastigmine patch in patients with mild-to-moderate AD has been previously investigated [24,25]. An open-label study reported no marked differences in the safety or efficacy of combination therapy with 9.5 mg/24 h rivastigmine patch and memantine compared with 9.5 mg/24 h rivastigmine patch alone in patients with mild-to-moderate AD [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of concomitant memantine use on the efficacy, safety and tolerability of 9.5 mg/24 h rivastigmine patch in patients with mild-to-moderate AD has been previously investigated [24,25]. An open-label study reported no marked differences in the safety or efficacy of combination therapy with 9.5 mg/24 h rivastigmine patch and memantine compared with 9.5 mg/24 h rivastigmine patch alone in patients with mild-to-moderate AD [24].…”
Section: Discussionmentioning
confidence: 99%
“…An open-label study reported no marked differences in the safety or efficacy of combination therapy with 9.5 mg/24 h rivastigmine patch and memantine compared with 9.5 mg/24 h rivastigmine patch alone in patients with mild-to-moderate AD [24]. Furthermore, post-hoc analysis of a 25-week, randomized, open-label study reported a non-significant increase in the incidence of AEs in patients with mild-to-moderate AD treated with 9.5 mg/24 h rivastigmine patch plus memantine, compared with memantine alone (73.3% versus 67.5%) [25].…”
Section: Discussionmentioning
confidence: 99%
“…This study is based on the EXelon Patch and combination with the mEmantine Comparative Trial (EXPECT) study, which was a randomized, multicenter, parallel group, open-label trial of the rivastigmine transdermal patch or memantine add-on treatment in probable AD patients [11,12]. The study duration was 24 weeks and included a 16-week randomized study with an 8-week run-in period.…”
Section: Methodsmentioning
confidence: 99%
“…Several clinical studies demonstrate that combined treatment with memantine and ChEI is safe and well-tolerated [58]. Indeed, efficacies of both drugs in AD patients have already been investigated.…”
Section: Discussionmentioning
confidence: 99%